Health strategies for working women - Sherman, Merlene (Crisp Pub. Menlo ParkUS, 1991)
Section I offers success strategies for family relationships; guidelines for parenting, inluding single parenting; and understanding aging parents. Includes tips for enjoying better financial health and friendships, and dealing with harassment. Sections II & III provide information about conditions and diseases e.g. sleep deprivation, stress, breast cancer, and osteoporosis, which sometimes afflict women; and Sections include action plans for implementing success and wellness strategies.